RESPON PEMBERIAN PUPUK ORGANIK CAIR (POC) URIN KELINCI PADA MEDIUM GAMBUT TERHADAP PERTUMBUHAN SEMAI GAHARU (Aquilaria malaccensis) - Mufidah Aulia; M. Mardhiansyah; Viny Volcherina darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Aquilaria malaccensis is a group of plants that produce highly commercial aromatics which lately has been difficult to obtain, efforts have been made to increase the productivity of gaharu plants by improving the quality of planting media and increasing seedling growth. It is done by giving liquid organic fertilizer from rabbit urine. The purpose of this research was to determine the effect and the best concentration of rabbit urine liquid organic fertilizer (LOF) use on peat medium, on the growth of Aquilaria malaccensis seedlings. This study used a complet random design (CRD) consisting of 4 treatments and 5 replications, in order to obtain 20 experimental units. The treatments were: K0 (control) K1 (rabbit urine with 20% concentration) K2 (rabbit urine with 50% concentration) K3 (rabbit urine with 80% concentration). The data were further analyzed using variance, with SPSS software version 23.0, the test was conducted to determine whether at least one treatment that had a significant effect. If there is, it must be continued with the DNMRT test at 5% level. The application of rabbit urine liquid organic fertilizer (LOF) affected the growth of Aquilaria malaccensis seedlings, and the best concentration of rabbit urine liquid organic fertilizer (LOF) to stimulate the growth of Aquilaria malaccensis seedlings on peat medium was at 20% concentration (Treatment K1) with the seedling survival rate of 88%, increase in seedling height 3.05 cm, and top root ratio 4.67.Keywords : Liquid organicfertilizer, rabbiturine,Aqularia malaccensis,peatmedium